The Evaluation of Use Photovoltaics (PV) in Renewable Energy Technology as Sustainability Strategies - Ulul Azmi; Nugroho Adi Sasongko; Sri Murtiana; Guntur Eko Saputro (CV. AFDIFAL MAJU BERKAH, 2024)
The United Nations (UN) proposed the Sustainable Development Goals (SDGs) to make the earth peaceful and prosperous by 2030. Abundant water and food supply, sustainable energy consumption, climate change mitigation, and sustainable energy consumption are considered the keys to better sustainability. For example, the food sector is responsible for 30% of global energy consumption, 21-37% of greenhouse gas (GHG) emissions, and 70% of global water withdrawals. Integrating renewable energy into a country's energy mix largely depends on the implementation of renewable energy policies. Sustainably developed solar photovoltaic options to meet energy. The main focus is to achieve energy security and independence with special emphasis on solar energy, to drive transformative change towards widespread adoption of renewable energy. The research method uses a literature study and the findings are in the form of the direction of the Indonesian Government's policy setting, namely the National Energy General Plan (RUEN) which is the basis for regulation through Presidential Regulation Number 79 of 2014 with the aim of changing the increase in the national energy share to 23% by 2025. This regulation aims to create opportunities for PT PLN (Persero) customers in the household, business, government, social, and industrial sectors to be actively involved in the utilization and management of renewable energy in a sustainable manner and provide insight into the sustainability of solar energy, including environmental and economic development.